Are the impacts of carbon nanotubes enhanced in Mytilus galloprovincialis submitted to air exposure? - Andrade, Madalena (2018)
Intertidal species are frequently exposed to environmental changes associated with multiple stressors, which they must either avoid or tolerate by developing physiological and biochemical strategies. Some of the natural environmental changes are related with the tidal cycle which forces organisms to tolerate the diﬀerences between an aquatic and an aerial environment. Furthermore, in these environments, organisms are also subjected to pollutants from anthropogenic sources. The present study evaluated the impacts in Mytilus galloprovincialis exposed to multi-walled carbon nanotubes (0.01mg/L MWCNTs) when continuously submersed or exposed to tides (5h of low tide, 7h of high tide) for 14 days. Our results demonstrated that mussels were physiologically and biochemically aﬀected by MWCNTs, especially when exposed to tides. In fact, when only exposed to the carbon nanoparticles oronly exposed to tides,the stress induced was notenough to activate mussels’ antioxidant defenses which resulted in oxidative damage. However, when mussels were exposed to the combination of tides and MWCNTs increased metabolism was observed, associated with a possible higher production of reactive oxygen species (ROS), leading to a signiﬁcant increase in the activities of antioxidant enzymes (superoxide dismutase, SOD and glutathione peroxide, GPx) and oxidized glutathione content (GSSG), preventing the occurrence of cellular damage, expressed as no lipid peroxidation (LPO) or protein carbonylation (PC). Therefore, organisms seemed to be able to tolerate MWCNTs and air exposure during tidal regime; however, the combination of both stressors induced higher oxidative stress. These ﬁndings indicate that the increasing presence of carbon nanoparticles in marine ecosystems can induce higher toxic impacts in intertidal organisms compared to organisms continuously submerged. Also, our results may indicate that air exposure can act as a cofounding factor on the assessment of diﬀerent stressors in organisms living in coastal systems.